Pengaruh Aset dalam Perkembangan Usaha Kecil Terhadap Pendapatan Usaha Mikro Kecil Menengah Kota Lhokseumawe Di Era Pandemi Covid 19 - Isra Maulina; Sufrizal; Iskandar (IAIN Langsa, 2022)
Income is the level of a person's ability to meet the needs of life in a certain period of time, usually within one month. This study aims to determine the effect of assets on UMKM income in the era of the covid 19 pandemic. The population in this study is UMKM in the City of Lhokseumawe which are registered with the Office of Industry, Trade, Cooperatives and Small and Medium Enterprises of Lhokseumawe City in 2020. This research is a quantitative type, The sampling technique is purposive sampling, namely the population that meets certain sample criteria according to what is desired, the sample in this study is 78 small business units, UMKM. The results of the study prove that the results of the partial test (t) The value of the regression coefficient for the asset variable shows a positive direction, namely the effect of assets on income is significant where the value of tcount (65.842) ˃ ttable (1.99210) and a significance of 0.000 ˂ 0.05, so Ho is rejected and Ha accepted UMKM income in the era of the covid 19 pandemic and The results of the study prove that the results of the test for the coefficient of determination (R2) show that the ability of asset variables to explain UMKM income variables is 98.3%, while the remaining 1.7% is explained by other factors outside this research model (small business).